1945
DOI: 10.1021/i560147a001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Nitrogen by Combustion Improved Dumas Apparatus and Recycle Procedure

Abstract: Improved apparatus and procedure are described for the determination of nitrogen b y combustion according to. the method of Dumas.The improvements permit a rapid, highly accurate analysis of organic materials, particularly petroleum products, containing 0.01 to 50% nitrogen, regardless of whether the sample is a gas, liquid, or solid. The possible incomplete combustion of methane formed b y thermal cracking is overcome by recycling a mixture of the combustion products and pure oxygen through the combustion tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1952
1952
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In 1947 Wanntorp and Nordlund (19) used saponification and adsorption on Floridin for the removal of fat and the carotenoids, but recovered only 92% of added «-tocopherol. The more recent assay of Quaife and Dju (13) requires a molecular still and the use of hydrogenation, which is prohibited in certain hospitals (3). The present procedure combines elements of these two methods; it is easy to perform, requires only readily available equipment, and yields an over-all recovery of 98% of added «-tocopherol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1947 Wanntorp and Nordlund (19) used saponification and adsorption on Floridin for the removal of fat and the carotenoids, but recovered only 92% of added «-tocopherol. The more recent assay of Quaife and Dju (13) requires a molecular still and the use of hydrogenation, which is prohibited in certain hospitals (3). The present procedure combines elements of these two methods; it is easy to perform, requires only readily available equipment, and yields an over-all recovery of 98% of added «-tocopherol.…”
Section: Discussionmentioning
confidence: 99%
“…Gonick et al: (3) state that high nitrogen results can be caused by the release of adsorbed nitrogen on copper oxide when the latter is reduced to the metallic state by burning the sample. They do not state how large such errors are.…”
Section: Discussionmentioning
confidence: 99%
“…All laboratories indicated that the method was not applicable to petroleum samples containing less than 0.5% nitrogen. It appears that erratic values may be the result of incomplete combustion (18)•, Laboratory 5 found methane in the combustion products from all samples, but using the gas recycle procedure (5) obtained excellent results. Laboratories 8 and 9 used a double furnace modification (9, 20) to obtain accurate data.…”
Section: Temperaturementioning
confidence: 99%
“…Combustion of methane is ensured by an auxiliary combustion tube filled with highly active copper oxide (8). Pyrolysis of the sample is carried out byr a traveling electric furnace (3,10) in a stream of carbon dioxide, and any' carbonaceous residue is then completely burned in a stream of oxygen as described by' Gonick et al (2). This technique eliminates the necessity for mixing the sample with copper oxide or other oxidation aids when testing refractory compounds (11).…”
mentioning
confidence: 99%
“…In order to maintain a satisfactorily low blank value it is necessary that the carbon dioxide used as a sweep gas contain not more than 0.01 volume % of nitrogen or other inert gases. This requirement is satisfied when carbon dioxide is prepared from the solid, liquefied in a pressure vessel essentially as described by Gonick et al (2). The vessel used for this purpose has a capacity of 150 pounds of solid carbon dioxide, which provides a sufficient supply of gas to operate the unit for several years.…”
mentioning
confidence: 99%